Análisis de financiamiento para la apertura de una sucursal en la ciudad de Machala, provincia de El Oro. - Gomez Sigsig, Johnny Fernando (My University, 2019)
The present investigation allows to demonstrate several existing investment options for the creation of an establishment in the city of Machala. You want to look for the best financing option available in the market that meets the requirements demanded by the borrower. Several banking entities were analyzed that allow to make appropriate credits for the commercial scope and in which the credit for fixed assets was accepted as the most indicated. In addition, elements such as interest rates and terms that allow the debt to be more flexible have been taken into account. Once the information and data have been obtained, the company can choose the best decision according to their needs and requirements and the one that has been taken as a financing entity to the Corporación Financiera Nacional.
La presente investigación permite demostrar varias opciones de inversión existentes para la creación de un establecimiento en la ciudad de Machala. Se desea buscar la mejor opción de financiamiento existente en el mercado que cumpla con los requerimientos exigidos por el acreditado. Se analizaron varias entidades bancarias que permitan realizar créditos apropiados para el ámbito comercial y en el que se aceptó al crédito por activo fijo como el más indicado. Además se ha tomado en cuenta elementos como tasas de interés y plazos que permitan que sea más flexible la deuda. Una vez obtenida la información y datos, la empresa puede elegir la mejor decisión según sea sus necesidades y requerimientos y la que se ha tomado como entidad financiadora a la Corporación Financiera Nacional.
Keywords: FINANCIAMIENTO; ANUALIDAD; CRÉDITO; INVERSIÓN; INTERÉS